2006
DOI: 10.2151/jmsj.84a.113
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Wind Characteristics in Precipitating Cloud Systems over West Sumatera, Indonesia, Observed with Equatorial Atmosphere Radar: Case Study of 23-24 April 2004 during the First CPEA Campaign Period

Abstract: Characteristics of vertical wind profiles (VWPs) in precipitating clouds were studied over western Sumatera (or Sumatra) Island of the Indonesian maritime continent during the first Coupling Process VWPs were precisely measured with the EAR directly in precipitating clouds, which were identified using simultaneous XDR observation. A super-cloud cluster (SCC) system of the intraseasonal variation (ISV) onset phase was examined as a case study. The SCC consisted of three cloud clusters (CCs), which were further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 29 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Profiler retrievals from Darwin have further shown that non-precipitating anvil has potentially different vertical motion structure than precipitating stratiform cloud (Protat and Williams, 2011). Other profiler studies have been conducted over southern India and Indonesia (Kumar et al, 2005;Mori et al, 2006;Rao et al, 2009;Uma and Rao, 2009;Abhilash et al, 2010;Uma et al, 2012) and are generally consistent with the Darwin findings. In addition, Giangrande et al (2013) used profiler retrievals to analyse the statistics of deep convective vertical velocities over a midlatitude continental site and found updraught core maxima regularly exceed 10 m s −1 , although downdraught core maxima were skewed to lower values and found at lower heights.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Profiler retrievals from Darwin have further shown that non-precipitating anvil has potentially different vertical motion structure than precipitating stratiform cloud (Protat and Williams, 2011). Other profiler studies have been conducted over southern India and Indonesia (Kumar et al, 2005;Mori et al, 2006;Rao et al, 2009;Uma and Rao, 2009;Abhilash et al, 2010;Uma et al, 2012) and are generally consistent with the Darwin findings. In addition, Giangrande et al (2013) used profiler retrievals to analyse the statistics of deep convective vertical velocities over a midlatitude continental site and found updraught core maxima regularly exceed 10 m s −1 , although downdraught core maxima were skewed to lower values and found at lower heights.…”
Section: Introductionmentioning
confidence: 56%
“…Profiler retrievals from Darwin have further shown that non‐precipitating anvil has potentially different vertical motion structure than precipitating stratiform cloud (Protat and Williams, ). Other profiler studies have been conducted over southern India and Indonesia (Kumar et al ., ; Mori et al ., ; Rao et al ., ; Uma and Rao, ; Abhilash et al ., ; Uma et al ., ) and are generally consistent with the Darwin findings. In addition, Giangrande et al .…”
Section: Introductionmentioning
confidence: 99%
“…Diurnally developed convections and local circulations over the IMC have been studied widely, in particular over equatorial western Sumatera Island (e.g., Wu et al 2003Wu et al , 2009aMori et al , 2006Mori et al , 2011Sakurai et al 2005Sakurai et al , 2009Sakurai et al , 2011Shibagaki et al 2006a;Hamada et al 2008;Kawashima et al 2011) and in relation to intraseasonal variations (ISVs) including the Madden-Julian oscillation (MJO, Madden and Julian 1972) (e.g., Shibagaki et al 2006b;Fujita et al 2011;Kamimera et al 2012). These studies were based on a number of campaignrelated observations that were collected by using X-band Doppler radars, intensive atmospheric soundings, rain gauge networks, disdrometers, and surface weather stations, as well as satellite observations.…”
Section: Introductionmentioning
confidence: 99%
“…The structure and dynamics of convective cells have been studied in detail using an X-band Doppler radar (XDR), Equatorial Atmosphere Radar (EAR) and intensive soundings Mori et al 2006;Sakurai et al 2009a;Shibagaki et al 2006). However, convection over the southwestern coastal region of the island, which is an essential region for our study, was not covered by the XDR because of the complicated high topography around the XDR and EAR.…”
Section: Introductionmentioning
confidence: 99%